NGOs and rural development: theory and practice - Bhose,Joel S.G.R. (New Delhi, 2003)
This book attempts to examine the role of NGOs in the rural development. Tracing the genesis and evolution of voluntary organisations, it evolves a theory of voluntarism such as sacrificial, professional, amateur, ventilatory, survival, pseudo and trans-figuration voluntarism. In addition to discussing framework and types of NGOs, the author throws substantial light on the concept of rural development and NGOs, interventions in it. Also, he provides valuable information on people's participation in rural development, importance of empowering rural people and the need for advocacy to influence government policies in favour of the poor. NGOs and Rural Development: Theory and Practice will serve as a manual for persons working in NGOs, representatives of funding agencies, government officials, students and teachers of social work.
Keywords: Rural development